Deleuze and religion - Bryden, Mary, 1953- (London ; New York : Routledge, 2001)
This collection of essays explores the religious implications and connections of Deleuze's thinking. It sets his writing in the context of a wide spectrum of textual material, including patristics, mysticism, dogmatic theology and literature.
Betrayal of God / Ronald Bogue -- Organism as the judgement of God : Aristotle, Kant and Deleuze on nature (that is, on biology, theology and politics) / John Protevi -- Embodied anti-theology : the body without organs and the judgement of God / Judith Poxon -- Scattering of time crystals : Deleuze, mysticism and cinema / Michael Goddard -- Tibetan Book of the Dead : Deleuze and the positivity of the second light / N. Robert Glass -- Thinking difference : a comparative study of Gilles Deleuze, Plotinus and Meister Eckhart / Oliver Davies -- Bodily organs and organisation / Maximillan de Gaynesford -- Nietzsche's arrow : Deleuze on D.H. Lawrence's Apocalypse / Mary Bryden -- Future of an illusion : Melville's deconstruction of Deleuze's a/theology / Thomas Cousineau -- Knowing one's enemy : Deleuze, Artaud, and the problem of judgement / Catherine Dale -- Pure reserve : Deleuze, philosophy, and immanence / Keith Ansell Pearson -- Why is philosophy so compromised with God? / Philip Goodchild -- Doctrine of univocity : Deleuze's ontology of immanence / Daniel W. Smith -- Deleuze's impersonal, hylozoic cosmology : the expulsion of theology / Eliot Albert.
Includes bibliographical references and index.
Print version record.
Master record variable field(s) change: 082
Keywords: Deleuze, Gilles; Deleuze, Gilles; Deleuze, Gilles; Deleuze, Gilles, -- 1925-1995.; Deleuze, Gilles; Philosophy and religion; Philosophie et religion; PHILOSOPHY -- History & Surveys -- Modern; Philosophy and religion; Godsdienst; Religionsphilosophie; Electronic books